2017
DOI: 10.1007/s10943-017-0467-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Spiritual Well-Being and Hope in Patients with Cardiovascular Disease

Abstract: Spirituality and hope have been identified as important constructs in health research, since both are thought to enhance a person's ability to cope with the consequences of serious illness. The aim of this study was to examine the relationship between spiritual well-being and hope in patients with cardiovascular disease. Using descriptive, correlational methodology, the investigator gathered data on a convenience sample of 500 patients with cardiovascular disease who were hospitalized in a medical institution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 24 publications
4
23
1
6
Order By: Relevance
“…In some studies on university students , there was no significant difference between the sexes as in this study. Regarding spiritual well-being, there are no gender differences in this study although there are findings that women are better at spiritual well-being (Yaghoobzadeh, 2018). It is estimated here that theological education can have a positive contribution to both self-handicapping and spiritual well-being, not creating gender disparity.…”
Section: Discussioncontrasting
confidence: 50%
“…In some studies on university students , there was no significant difference between the sexes as in this study. Regarding spiritual well-being, there are no gender differences in this study although there are findings that women are better at spiritual well-being (Yaghoobzadeh, 2018). It is estimated here that theological education can have a positive contribution to both self-handicapping and spiritual well-being, not creating gender disparity.…”
Section: Discussioncontrasting
confidence: 50%
“…Religiosity. The measure of religiosity was adapted and simplified from empirically validated survey scales developed by nursing researchers to prevent potential burden to respondents due to their age [59]. Participants were asked to rate each item in the questionnaire using a 10-point Likert-type scale.…”
Section: Methodsmentioning
confidence: 99%
“…Various studies on different patient groups have examined what facilitates and what hinders hope. An Iranian study on hope and spirituality in patients with cardiovascular diseases, found a stronger hope among those being married, having higher education, good economic status and with stronger spiritual well-being [32]. This study concluded that multiple factors may influence on hope.…”
Section: Factors That Can Facilitate or Hinder Hopementioning
confidence: 64%